1993
DOI: 10.1002/1098-108x(199312)14:4<403::aid-eat2260140403>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of DSM-III-R eating disorders and personality disorders

Abstract: The purpose of this study was to assess the relationship of eating disorders to personality disorders. Two hundred subjects were independently administered the Structured Clinical Interview for DSM‐III‐R (SCID) and the Personality Disorder Examination (PDE) face‐to‐face by two experienced clinicians. One hundred forty‐six also completed the Personality Diagnostic Questionnaire‐Revised (PDQ‐R). Rates of personality disorder among patients with and without eating disorders were determined by each of the three in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
2
12

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(55 citation statements)
references
References 15 publications
(44 reference statements)
4
37
2
12
Order By: Relevance
“…Therefore, they cannot be generalized to males or to ED patients who present to specialty clinics for treatment. Given our recruitment focus (du Fort, Norman, & Bland, 1993), the rates of PD in our ED patients are higher than the rates reported in clinic samples (see reviews by Grilo, 2002;Skodol et al, 1993;Vitousek & Manke, 1994, for discussions of the extent and variability of co-occurrences among EDs and PDs across recruitment methods). Fairburn, Welch, Norman, O'Connor, and Doll (1996) reported differences in the patterns of psychopathology observed for patient (clinicrecruited) versus community samples of EDs, whereas Wilfley, Pike, Dohm, StriegelMoore, and Fairburn (2001) did not.…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, they cannot be generalized to males or to ED patients who present to specialty clinics for treatment. Given our recruitment focus (du Fort, Norman, & Bland, 1993), the rates of PD in our ED patients are higher than the rates reported in clinic samples (see reviews by Grilo, 2002;Skodol et al, 1993;Vitousek & Manke, 1994, for discussions of the extent and variability of co-occurrences among EDs and PDs across recruitment methods). Fairburn, Welch, Norman, O'Connor, and Doll (1996) reported differences in the patterns of psychopathology observed for patient (clinicrecruited) versus community samples of EDs, whereas Wilfley, Pike, Dohm, StriegelMoore, and Fairburn (2001) did not.…”
Section: Discussionsupporting
confidence: 78%
“…Notably, a constricted/overcontrolled type emerged characterized by behavioral inhibition, limited psychological insight, constricted emotional expression, shyness in social situations, anxiousness, and distortions in body image. This convergence, however, contrasts sharply with rates of categorically based personality disorder diagnoses in the group for which estimates range from 21% to 97% (Skodol et al, 1993;Vitousek & Manke, 1994). Despite this inconsistency, there is consensus that the anxious/fearful personality cluster predominates in AN (Wonderlich et al, 2005).…”
Section: Overview Of the Phenotypic Expression Of Anmentioning
confidence: 99%
“…Findings have indicated that obese individuals who regularly binge exhibit more weight-related and general psychopathology than nonbinging obese individuals Kolotkin, Revis, Kirkley, & Janick, 1987;Marcus et al, 1990;Skodol et al, 1993;Spitzer et al, 1993;StriegelMoore, Wilson, Wilfley, Elder, & Brownell, 1998;Telch & Agras, 1994;Telch & Stice, 1998;Wadden, Foster, Letizia, & Wilk, 1993;Wilfley et al, 2000;Yanovski, Nelson, Dubbert, & Spitzer, 1993). In addition, they consume more calories than nonbinging obese women in a controlled setting (Goldfein, Walsh, LaChaussee, Kissileff, & Devlin, 1993;Yanovski et al, 1992).…”
Section: Introductionmentioning
confidence: 99%